Infectious Disease Images: A Remarkable, Free Resource. (10th November 2021) - Radcliffe, Christopher; Grant, Matthew
Abstract: Infectious Disease Images (idimages.org) features several hundred with a vast array of diagnoses. The website is organized by cases and images and boasts an atlas with scores of bacteria, viruses, fungi, parasites, and ectoparasites. As a free resource, Infectious Disease Images lends itself nicely to both learners and educators at all levels.